A Comparison of Taxonomies for Model Transformation Languages (2010)
Since the introduction of the MDE/MDA/MDD ideas for software systems development several years ago, a number of different (meta)modeling and model transformation languages have been proposed. Although the OMG's QVT standard specification has somewhat stabilized the number of new model transformation languages, it is likely that new ones will continue to appear, following different paradigms and approaches. However, the evolution towards the consolidation of models as a unifying, foundational and consistent concept for software-intensive system development, requires the realization of a set of ideal characteristics for the specification of model transformation languages. Several works have been proposed for defining characterization and classification schemes, and the set of these ideal characteristics.